Exploring the Impact of Optional Mathematics on Career Readiness and Cognitive Development in Non-Stem Secondary Education in North-East Region Nigeria - Hassan , Muhammad; Niyi , Olonrunsola Oriola (Kashere Journal of Education, 2025)
This study investigates the implications of allowing secondary school students in Nigeria to opt out of mathematics and how this choice affects their cognitive development and career readiness, particularly among non-STEM learners. Based on Cognitive Development Theory, the study utilised a survey design to assess whether the avoidance of mathematics diminishes students' abilities in critical thinking, analytical reasoning, and long-term career readiness. A total of 420 students and 22 teachers from public and private schools across six states in the Northeast region of Nigeria participated in the study. Data were gathered using two standardised instruments: a Cognitive Skills Assessment (24 items) and a Career Readiness Competency Scale (28 items). Both instruments demonstrated high internal consistency, with Cronbach’s alpha values of 0.83 and 0.85 respectively. Data analysis, conducted using the Statistical Package for the Social Sciences (SPSS), involved descriptive statistics, independent t-tests, and ANOVA to compare students who avoided mathematics with those who continued studying it. Findings revealed that students who opted out of mathematics recorded significantly lower cognitive development scores (M = 59.4%) compared to peers who continued with mathematics (M = 74.8%). They also demonstrated weaker indicators of career readiness, particularly in critical thinking, quantitative reasoning, and structured problem-solving (p < 0.05). Based on these outcomes, the null hypothesis, which stated that opting out of mathematics has no effect on cognitive ability or career readiness, was rejected. The study concludes that avoiding mathematics diminishes students’ cognitive strength, limits their analytical capacity, and ultimately weakens their preparation for diverse career pathways.